The Clinical Characteristics of Orbital Inflammation Patients at a Tertiary Hospital in East Java, Indonesia - Karina Anggia dewi; Delfitri Lutfi; Kusuma Eko Purwantari; Indri Wahyuni; Yana Rosita (Universitas Airlangga, Surabaya, Indonesia, 2026)
Background: Orbital inflammation is a benign inflammatory condition affecting eye socket, including orbital soft tissue, ocular muscles, and optic nerve. Diagnosing orbital inflammation is challenging due to the lack of standardized clinical criteria and overlapping possibility with other orbital diseases. Objective: To analyze the clinical characteristics of orbital inflammation disease. Materials and Methods: This retrospective, observational, and analytical study focused on patients diagnosed with orbital inflammation. The authors classified and analyzed data from 68 samples that met the inclusion and exclusion criteria based on descriptive statistics. We used the Chi-square test and Odds Ratio (OR) to evaluate correlations between clinical variables. We only included variables with a sufficiently balanced data distribution in the correlation analysis to meet the assumptions of the Chi-square test, including proptosis, visual impairment, red eye, and orbital pain. Results: Most patients were female (55.9%) and within the 18-75 age group (97.1%). Orbital inflammation predominantly presented unilaterally (89.7%). The most frequent clinical characteristics were proptosis, red eyes, decreased vision, and orbital pain. Proptosis and red eye demonstrated the most significant correlation, followed by proptosis and dry eye, red eye and eyelid edema, and proptosis and ptosis, respectively. Conclusion: The identified key clinical characteristics of orbital inflammation are proptosis, red eyes, decreased vision, and orbital pain. The most significant correlation has been identified between proptosis and red eye, followed by proptosis and dry eye, red eye and eyelid edema, and proptosis and ptosis, respectively. These clinical features, when found together, support clinicians in recognizing and establishing a diagnosis of orbital inflammation.